Phenotypic Diversity in Nepalese Finger Millet (Eleusine coracana (L.) Gaertn.) Landraces - Thapa, Pradip; Bohara, Sandip; Acharya, Suprava; Kawar, Aakriti; Adhikari, Alina; Shrestha, Promise; Joshi, Bal Krishna; Poudyal, Damodar (Genetics, Plant Breeding and Seed Science, 2025)
Finger millet (Eleusine coracana (L.) Gaertn.), a nutritionally rich and climate-resilient crop, remains underutilized in modern breeding programs despite its broad agroecological adaptability and genetic diversity. This study aimed to characterize phenotypic diversity among 72 finger millet landraces collected from 19 districts of Nepal. Field evaluation was conducted at the National Agriculture Genetic Resources Centre, Khumaltar, during the 2021–2022 growing season using an augmented block design with two replications. A total of 23 quantitative and 9 qualitative traits were assessed following the IBPGR descriptors. Statistical analyses of the collected dataset included descriptive statistics, the Shannon–Weaver diversity index (H′), principal component analysis (PCA), K-means clustering, and phenotypic path analysis. Substantial variability was observed across agro-morphological traits, with CV ranging from 3.98% to 37.99% and H′ from 0.59 to 0.93 for quantitative traits, and from 0.18 to 0.98 for qualitative traits. PCA revealed that the first seven components (eigenvalue >1) explained 76.8% of total phenotypic variation, with PC1 and PC2 contributing 43.83%. Cluster analysis based on the average method and Euclidean distance delineated three clusters, with Cluster 1 comprising 93% of accessions characterized by superior yield traits including fingers per ear (7.10), ear weight (10.20 g), thousand-seed weight (2.88 g), and grain yield (2.47 t/ha). Path coefficient analysis indicated that fourth leaf breadth and flag leaf length exerted strong positive direct effects on grain yield, while the area of the fourth leaf and finger width had negative effects. Promising landraces including CO12712 (3.89 t/ha), CO12570 (3.62 t/ha), and CO13039 (3.59 t/ha) were identified as potential candidates for future varietal improvement. The findings underscore the high phenotypic diversity and agronomic potential of Nepalese finger millet landraces. Integrating phenotypic, molecular, and multi-environment data is suggested to improve the genetic potential of finger millet in breeding programs.